2017
DOI: 10.19045/bspab.2017.600127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seed rates on the growth and yield of different sunflower varieties

Abstract: The study was conducted at student's Experimental Farm, Department of Agronomy, Sindh Agriculture University Tandojam to evaluate growth and yield of sunflower varieties as affected by seed rates during 2015. The experiment was laid out three replicated randomized complete block design (RCBD) Factorial. The treatments included 03 seed rates and 03 sunflower varieties. Net plot size was used in the experiment 3m x 3m = 9m 2 . The seed rates were kept as Factor A (S1 = 5 kg, S2 = 7.5 kg and S3 = 10 kg ha -1 ) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…Allam and Galal, (1996); Salehi and Bohrani, (2000); Al-Thabet, (2006) dedicated that decreasing in plant density was led to an increase in head diameter which results are similar with our study. Several studies have reported that with increasing plant density decreases head diameter but increasing plant density enhances the seed yield (Johnson et al 2010;Jahangir et al 2006;Panhwar et al 2017). Modanlo et al (2021) reported that, with increasing plant density yield and oil yield have effected positively but, head diameter, plant height, 100grain yield and grain yield per plant were decreased with increasing plant density.…”
Section: Resultsmentioning
confidence: 99%
“…Allam and Galal, (1996); Salehi and Bohrani, (2000); Al-Thabet, (2006) dedicated that decreasing in plant density was led to an increase in head diameter which results are similar with our study. Several studies have reported that with increasing plant density decreases head diameter but increasing plant density enhances the seed yield (Johnson et al 2010;Jahangir et al 2006;Panhwar et al 2017). Modanlo et al (2021) reported that, with increasing plant density yield and oil yield have effected positively but, head diameter, plant height, 100grain yield and grain yield per plant were decreased with increasing plant density.…”
Section: Resultsmentioning
confidence: 99%
“…These outcomes are a result of shade brought on by the various sunflower types' varying plant heights. According to Panhwar et al (2017), there is a significant variation in plant height between different sunflower cultivars.…”
Section: A: Sugar Beet: 1-effect Of Sunflower Cultivars On Sugar Beetmentioning
confidence: 99%